Survival outcomes in patients with de novo metastatic Merkel cell carcinoma according to site of metastases - Khaddour, Karam; Liu, Mofei; Kim, Emily Y.; Bahar, Furkan; Lôbo, Matheus M.; Giobbie-Hurder, Anita; Silk, Ann W.; Thakuria, Manisha (Frontiers in Oncology, 2024)
IntroductionMerkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine malignancy of the skin with a predilection for metastases. This study investigates the clinical outcomes in patients presenting with de novo Stage IV MCC according to the metastatic site(s) at presentation.Materials and methodsPatients who presented with one or more sites of distant metastatic MCC at initial diagnosis between 2009 and 2023 were identified. The presence or absence of one or more metastases in each organ was categorized for each patient at the time of diagnosis. Overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan-Meier method. Competing risk analysis was used to estimate the cumulative occurrence risk of MCC-specific death. Fisher’s exact test was used for response rate analysis. Results were considered statically significant if p < 0.05.ResultsThirty-four patients presented with de novo distant metastatic MCC. There was no association between the number of metastatic sites at diagnosis and OS (p= 0.58), PFS (p=0.79), or response rates (p=0.53). However, the presence of bone metastases was associated with significantly shorter OS (8.2 versus 25.2 months, HR: 2.4, 95% CI 1.01-5.7, p= 0.04). MCC-specific death in patients with lymph node metastases was significantly lower than in patients without (HR: 0.28, 95% CI: 0.09-0.87, p= 0.013). The presence of bone metastases tended to associate with an increased risk of MCC-specific death, although not statistically significant. The location of metastases was not associated with the response rate to first-line treatment. There was no significant association between site of metastases and PFS.ConclusionIn this cohort of patients with de novo metastatic MCC, the presence of bone metastases, but not the number of organs involved, was associated with significantly worse OS. The presence of lymph node metastases was associated with lower MCC-specific death. Further research is warranted in larger cohorts to investigate the impact of the location of metastases on clinical outcomes.